Feasibility of In-Vivo Simulation of Acute Hemodynamics in Human Atrial Fibrillation - Sramko, Marek; Wichterle, Dan; Kautzner, Josef (PloS one, 2016)
This study evaluated hemodynamic feasibility and reproducibility of a new method for in vivo simulation of human atrial fibrillation (AF). The method was tested during sinus rhythm in 10 patients undergoing catheter ablation for AF. A simple electronic device was assembled that allowed triggering a cardiac stimulator by predefined series of RR intervals. Irregular RR interval sequences with a mean heart rate of 90/min and 130/min were obtained from ECG recordings of another patients with AF. Simultaneous atrioventricular pacing was delivered by catheters placed inside the coronary sinus and at the His bundle region. Hemodynamic effect of the simulated AF was assessed by invasive measurement of the left ventricular (LV) pressure, dP/dt, and Tau. Compared to regular pacing at the same mean heart rate, the simulated AF significantly impaired the LV both systolic and diastolic function. Repeated AF pacing in the same patients generated similar LV hemodynamics. The proposed method provides a realistic and reproducible in-vivo model of AF. It can be exploited for investigation of the hemodynamic consequences of AF in various patient populations.
Keywords: nodus atrioventricularis; Heart; Female; Heart Ventricles; Atrial Fibrillation; Atrioventricular Node; ženské pohlaví; srdeční komory; Catheter Ablation; Hemodynamics; hemodynamika; srdce; lidé; katetrizační ablace; Electrocardiography; elektrokardiografie; Cardiac Pacing, Artificial; srdeční frekvence; Middle Aged; Male; Aged; fibrilace síní; lidé středního věku; senioři; mužské pohlaví; kardiostimulace umělá; Heart Rate; Humans